Perbedaan Pengaruh Media Edukasi Terhadap Kepatuhan Orang Tua Anak Cerebral Palsy Untuk Melaksanakan Home Program - Abdullah, Khabib; Amalia, Ichsanul; Wijaya, Aji Sukma (UI Scholars Hub, 2024)
Cerebral palsy (CP) is a condition of movement and function disorders in children that requires continuous physiotherapy. One factor in the successful development of children with CP is the existence of a home program/independent therapy carried out by parents at home. In providing the home program, physiotherapists at YPCP Surabaya gave leaflets to parents. However, this was less effective because it was easily damaged, so the home program media was replaced with video. The effectiveness of both in increasing parental compliance in carrying out the home program every day is not yet known. Objective: to find out the difference in parental compliance in carrying out a home program between using leaflet media or video media. Method: 20 parents of children with CP were randomly divided into leaflet groups and video groups, 10 people each. Each person is monitored for compliance in carrying out the home program for 1 week (7 days). Measurement of compliance with checklists every day. Results: parents in the video media group were more compliant in carrying out the home program than parents in the leaflet media group. Conclusion: video media is more effective in increasing the compliance of parents of children with CP in carrying out home programs compared to leaflet media.